RASIO KEUANGAN PENGARUHNYA TERHADAP PERTUMBUHAN LABA – STUDI PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA - FRIYANTO FRIYANTO (INSPIRASI : JURNAL ILMU-ILMU SOSIAL, 2023)
The purpose of this study was to determine the effect of financial ratios to profit growth at companies listed on the Indonesian Stock Exchange (BEI) in the period 2018-2020. Independent variables used is the Current Ratio, Net Profit Margin, Debt to Asset Ratio, Total assest Turnover. The population in this research is food and beverage companies listed in Indonesia Stock Exchange period 2018-2020. Data analysis techniques used in this research is multiple linear regression analysis. From the results of the regression analysis shows partially the Liquidity (Current Ratio) and Leverage (Debt to Asset Ratio) has negative effect on profith growth, while the activity ratio (Total Asset Turn Over) and profitability ratio (Net Profit Margin) has a positive effect on profith growth.